Cerebral microbleeds in idiopathic normal pressure hydrocephalus. Issue 1 (December 2015) - Johansson, Elias; Ambarki, Khalid; Birgander, Richard; Bahrami, Nazila; Eklund, Anders; Malm, Jan
Abstract Background A vascular disease could be involved in pathophysiology of normal pressure hydrocephalus (INPH). If so, there should be an association between INPH and cerebral microbleeds (CMB). This study aims to analyze if CMB are associated with INPH. Methods In this case-control study we included 14 patients with INPH (mean age 76 years, 60 % female) and 41 healthy controls (HeCo; mean age 71 years, 60 % female). All were investigated with magnetic resonance imaging (MRI) using a T2*-sequence. The MRI exams were reviewed by two neuroradiologists for the presence of CMBs; the prevalence of findings of two or more CMBs was compared between INPH group and control group. After investigation, INPH patients underwent shunt surgery. Results Two or more CMB were detected more frequently in the INPH group compared to HeCo (n = 6, 43 % vs. n = 4, 10 %;p = 0.01). Among the participants where MRI revealed CMB, the number of CMB was higher among the INPH patients than the HeCo (median 8; IQR 2-34 vs. median 1; IQR 1–2;p = 0.005). Conclusions This study supports a vascular component to the pathophysiology of INPH.